The Photocatalytic Activity of SiO2-TiO2/Graphite and Its Composite with Silver and Silver oxide - Fitria Rahmawati; Sayekti Wahyuningsih; Dian Irianti (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
This research study the mixed semiconductor of SiO2-TiO2 which was immobilized on graphite substrate and also studies the effect of surface modification on its mixed semiconductor. The surface modification was carried out by electrode position of Ag from 0.4 M of AgNO3 solution at various applied current. The electrode position was conducted for 30 minutes at 0.004; 0.008; 0.010; 0.012 and 0.014 A. In the electrode position cell, SiO2-TiO2/Graphite was used as cathode and a graphite rod was used as anode. The weight of deposited Ag was analyzed gravimetrically. The current efficiency of electrode position was calculated by comparing its experimental weight to its theoretical weight founded from calculation using Faraday’s equation for electrolytic cell. Meanwhile, the photo electrochemical testing was carried out to investigate the efficiency of induced photon to current conversion; it was measured as %IPCE (% Induced Photon to Current Efficiency). The crystallinity and crystal structure of the prepared materials were analyzed by X-ray diffraction and their surface morphology was analyzed by Scanning Electron Microscope (SEM). This research found that silver was deposited as silver metal, Ag and as silver oxide, AgO. The electrode position efficiency at applied current of 0.014 A is 92.30 % with diameter of cluster is 7 - 11.9 mm. It is founded that Ag and AgO deposition enhanced the efficiency of photon conversion into current up to 89.92 %. The optimum %IPCE value is at 28.6 % of Ag content. Ag-SiO2-TiO2/G has higher photo conversion than Ag-TiO2/G, shown by the %IPCE value at 300 nm is 83.25 % higher than Ag-TiO2/G. It indicates the significant role of silica network in photo excitation mechanisms in the composite material. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)